The Delayed Neuroprotective Effect of Methylene Blue in Experimental Rat Brain Trauma - Elizaveta E. Genrikhs; Elena V. Stelmashook; Dmitriy N. Voronkov; Svetlana V. Novikova; Olga P. Alexandrova; Mikhail V. Gulyaev; Nickolay K. Isaev (MDPI AG, 2020)
After traumatic brain injury (TBI), an increase in dysfunction of the limbs contralateral to injury focus was observed. Using different behavioral tests, we found that a single intravenous injection of methylene blue (MB, 1 mg/kg) 30 min after the injury reduced the impairment of the motor functions of the limbs from 7 to 120 days after TBI. Administration of methylene blue 30 min after the injury and then monthly (six injections in total) was the most effective both in terms of preservation of limb function and duration of therapeutic action. This therapeutic effect was clearly manifested from the seventh day and continued until the end of the experiment-by the 180th day after TBI. MB is known to possess antioxidant properties; it has a protective effect against TBI by promoting autophagy and minimizing lesion volume in the first two weeks after TBI. Studies of the brains on the 180th day after TBI demonstrated that the monthly treatment of animals with MB statistically significantly prevented an increase in the density of microglial cells in the ipsilateral hemisphere and a decrease in the thickness of the corpus callosum in the contralateral hemisphere in comparison with untreated animals. However, on the 180th day after TBI, the magnetic resonance imaging scan of the animal brains did not show a significant reduction in the volume of the lesion in MB-treated animals. These findings are important for understanding the development of the long-term effects of TBI and expand the required therapeutic window for targeted neuroprotective interventions.